2004
DOI: 10.1124/jpet.103.063974
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Chymase Inhibitor, 2-(5-Formylamino-6-oxo-2-phenyl-1,6-dihydropyrimidine-1-yl)-N-[{3,4-dioxo-1-phenyl-7-(2-pyridyloxy)}-2-heptyl]acetamide (NK3201), Suppresses Development of Abdominal Aortic Aneurysm in Hamsters

Abstract: In this study, we investigated the effect of a specific chymase inhibitor, 2-(5-formylamino-6-oxo-2-phenyl-1,6-dihydropyrimidine-1-yl)-N-[{3,4-dioxo-1-phenyl-7-(2-pyridyloxy)}-2-heptyl]acetamide (NK3201), in the development of abdominal aortic aneurysm in a hamster experimental model. The abdominal aortic aneurysm was induced by application of elastase onto the abdominal aorta in hamster. Each hamster was administered NK3201 (30 mg/kg/day p.o.) or placebo beginning 4 days before application of elastase and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…Chymase-positive mast cells were detected in the media and adventitia in human AAA (8). Pharmacological inhibition of chymase activity reduces AAA progression in hamsters (12). In addition to a unique set of proteases, mast cells also release proinflammatory cytokines (IFN-γ, TNF-α, and IL-4, -5, -6, and -13) and chemokines (monocyte chemoattractant protein-1 [MCP-1], IL-8, RANTES), all of which may directly or indirectly participate in AAA formation.…”
Section: Introductionmentioning
confidence: 99%
“…Chymase-positive mast cells were detected in the media and adventitia in human AAA (8). Pharmacological inhibition of chymase activity reduces AAA progression in hamsters (12). In addition to a unique set of proteases, mast cells also release proinflammatory cytokines (IFN-γ, TNF-α, and IL-4, -5, -6, and -13) and chemokines (monocyte chemoattractant protein-1 [MCP-1], IL-8, RANTES), all of which may directly or indirectly participate in AAA formation.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that chymase activity was significantly increased in human AAA, and that accumulated chymase-positive mast cells were observed in the media and adventitia [19]. A specific chymase inhibitor, 2-(5-formyamino-6-oxo-2 phenyl-1, 6-dihydropyrmidine-1-yl) N-[{3, 4-dioxo-1-phenyl-7-} 2-pyridyloxy]}-2heptyl] acetamide (NK3201), has been shown to suppress the development of AAA in hamsters (Tsunemi et al, 2004) [16]. Meanwhile, Yokokura et al (2007) reported that a new calcium antagonist, azelnidipine, may act via an anti-inflammatory mechanism in a rat AAA model, thus resulting in inhibition of aortic expansion.…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensin II plays an important role in the activation of inflammatory reactions in atherosclerosis (Miyazaki et al, 1999) [16][17]. Angiotensin II is generated from angiotensin I by two distinct types of angiotensin II-forming enzyme (ACE) and chymase in human cardiovascular tissues (Takai et al, 1999) [16][17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations